Housing prices, volatility, and fundamental value. (28th July 2021) - Tomat, Gian Maria
Abstract: Asset pricing theories imply the existence of a long run relation between real housing prices and rents. The long run relation predicts, that in each time period real housing prices should be equal to the expected present discounted value of subsequent real rents. We use the annual time series for the 1991–2016 period in Italy as evidence regarding the present discounted value relation. Considering the stochastic properties of the aggregate time series, cointegration tests do not deliver conclusive results. In a dynamic vector autoregression model, real housing prices are shown to properly anticipate forthcoming real rents, though they exhibit excess volatility. In the sample period, movements of housing prices relatively to the long run relation predict successive real returns. While rational speculative bubbles might produce excess volatility of housing prices, other explanations are required for the predictability of real housing returns.